Cyclic deformation and fatigue damage in single-crystal magnesium under fully reversed strain-controlled tension–compression in the [1 0 1¯ 0] direction. (February 2015) - Yu, Qin; Jiang, Yanyao; Wang, Jian
Abstract : Cyclic deformation and the resulting fatigue are experimentally investigated in single-crystal magnesium subjected to fully reversed strain-controlled tension–compression in the [1 0 1 ¯ 0] direction at room temperature. Plastic instability is found near the end of the first detwinning reversal. Twin–twin boundaries and secondary twins are induced by interaction of primary 1 0 1 ¯ 2 twins. Microcracks are developed at primary twin boundaries and twin–twin interaction sites. Final fracture is most likely caused by cleavage-cracking on the 1 0 1 ¯ 1–1 0 1 ¯ 2 double twin and shearing fracture on the basal plane.